2016
DOI: 10.9734/acri/2016/26600
|View full text |Cite
|
Sign up to set email alerts
|

GIS Suitability Analysis for Anaerobic Treatment Facility for Slaughter Houses in Anambra State of Nigeria

Abstract: Investment in anaerobic digestion of bio-energy plants for slaughterhouse wastes is a good venture from environmental, economical and sustainable view point. Several researches have been undertaken in biogas potential of various substrates in Nigeria, there is need therefore to undertake further research on other factors such as site suitability analysis to achieve renewable energy target in the study area. Site selection which is a critical step in actualizing viable bioenergy was carried out in the study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Location set covering models aim to find the lowest number of facilities such that every demand is covered by at least one facility within a pre-specified distance or travel time [29][30][31][32][33]. Despite the limited input data these models generally require, it remains necessary to define an explicit number of discrete demand nodes [32][33][34]. Notably, there are few literary references to continuous coverage problems, with most research limited to discrete applications [20].…”
Section: Location Set Covering Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Location set covering models aim to find the lowest number of facilities such that every demand is covered by at least one facility within a pre-specified distance or travel time [29][30][31][32][33]. Despite the limited input data these models generally require, it remains necessary to define an explicit number of discrete demand nodes [32][33][34]. Notably, there are few literary references to continuous coverage problems, with most research limited to discrete applications [20].…”
Section: Location Set Covering Modelmentioning
confidence: 99%
“…The introduced location-allocation models aim to find the optimal service location for fixed demand and supply patterns. Inherently to each of their optimization objectives (minimizing travel times [29], minimizing number of facilities [29][30][31][32][33] maximize coverage [20]), these models are geared towards finding a permanent location for a brick-and-mortar supply site with a long-term planning horizon.…”
Section: Vehicle Service Stop Allocationmentioning
confidence: 99%
“…These solid and liquid waste products are generated from the approximately 132 slaughterhouses spread across Nigeria (Nwanta, Onunkwo, Ezenduka, Phil-Eze, & Egege, 2008); and pose a high risk to the environment and public health due to lack of proper management. For instance, the analysis of the Nsukka metropolitan abattoir solid waste in South Eastern Nigeria showed that a total of 194 kg of solid (rumen/stomach) wastes were generated daily in its municipal abattoir without any clearly defined system of disposal and management (Chukwuma, Chukwuma, & Orakwe, 2016). Abattoir waste can be managed by channeling them towards biogas production.…”
Section: Abattoir Wastementioning
confidence: 99%
“…The buffer criteria for different restriction factors used in this research are based on the national standards of construction of buildings, commercial infrastructure, and secondary literature sources from previously published studies. Several secondary literature sources were referenced to find out the suitable distance for making buffers of all mentioned layers for restriction analysis as in Table 1 [20,22,[37][38][39][40]. The buffer criteria for different restriction factors used in this research are based on the national standards of construction of buildings, commercial infrastructure, and secondary literature sources from previously published studies.…”
Section: Restriction Analysismentioning
confidence: 99%